Assessment of the Implementation of Plastic and Styrofoam-Free Policy in Baguio City Public Market - Alexander G. Killip Jr.; Myshael Gem P. Dadulla (Research Synergy Foundation, 2023)
Plastic waste has been one of the pressing problems in Baguio City. Among the largest contributors to waste is the City's Public Market. The study's main objective is to assess the implementation of the Plastic and Styrofoam-free Policy of Baguio City in its public market to draft an action plan for its possible improvement. Specifically, it sought to determine the level of implementation of the Plastic and Styrofoam-free Policy by the technical working group from the City General Services Office; to determine the level of compliance with the Plastic and Styrofoam-free Policy among the registered stall owners in the public market; and to determine significant difference between the level of compliance among the different groups of registered stall owners in the public market according to their Line of business. The findings shall be a basis for preparing and proposing an action plan. The researchers used a quantitative research design, particularly the descriptive survey research method, and a survey questionnaire as a data collection method. The overall results showed that the ordinance must be implemented and complied with. Given this, the ordinance must be amended, allowing the use of biodegradable plastics as primary packaging for fresh and wet goods. Massive information dissemination thereof will heighten the implementation and compliance therewith.